Defining dormancy in mycobacterial disease. (July 2016) - Lipworth, S.; Hammond, R.J.H.; Baron, V.O.; Hu, Yanmin.; Coates, A.; Gillespie, S.H.
Summary: Tuberculosis remains a threat to global health and recent attempts to shorten therapy have not succeeded mainly due to cases of clinical relapse. This has focussed attention on the importance of "dormancy" in tuberculosis. There are a number of different definitions of the term and a similar multiplicity of different in vitro and in vivo models. The danger with this is the implicit assumption of equivalence between the terms and models, which will make even more difficult to unravel this complex conundrum. In this review we summarise the main models and definitions and their impact on susceptibility of Mycobacterium tuberculosis . We also suggest a potential nomenclature for debate. Dormancy researchers agree that factors underpinning this phenomenon are complex and nuanced. If we are to make progress we must agree the terms to be used and be consistent in using them.